Estimation of CPUE and CPUA of three caught fish by bottom trawler in the Motaf fishing grounds, Bushehr Province, Persian Gulf, Iran - SEYED MOHAMMAD SEYED HOSSEINI; SEYED YOUSEF PAIGHAMBARI; MOJTABA POULADI; MOHAMMAD JAVAD SHABANI (Biodiversitas Journal of Biological Diversity, 2018)
Seyed Hosseini SM, Paighambari SY, Pouladi M, Shabani MJ. 2018. Estimation of CPUE and CPUA of three caught fish by bottom trawler in the Motaf fishing grounds, Bushehr Province, Persian Gulf, Iran. Biodiversitas 19: 1434-1440. This study was conducted to estimate catch per unit effort (CPUE) and catch per unit area (CPUA) of Giant trevally (Caranx ignobilis Forsskål, 1775), Bigeye scad (Selar crumenophthalmus (Bloch, 1793), and Sulphur goatfish (Upeneus sulphureus (Cuvier, 1829). Sampling operations were done by a stern trawler in the Motaf fishing grounds located in the Persian Gulf during summer 2016. Overall, 36 hauls were done in two depths of 50-60 m and 60-70 m. In this research, the highest length frequencies of C. ignobilis, S. crumenophthalmus, and U. sulphureus were in the length classes of 56.5-61.5, 22-23.5 and 14-15.5 cm, respectively. The results of CPUE for C. ignobilis, S. crumenophthalmus, and U. sulphureus were 3, 0.159 and 0.078 kg h-1, while the results of CPUA were 45.03, 2.44 and 1.91 kg km-2, respectively. Also, CPUE values for mature and immature forms of C. ignobilis were 5.05 and 0.65 kg h-1, for S. crumenophthalmus were 0.2 and 0.07 kg h-1, and for U. sulphureus were 0.13 and 0.04 kg h-1, and CPUA values for C. ignobilis were 22.51 and 5.02 kg km-1, for S. crumenophthalmus were 22.03 and 10.95 kg km-1, and for U. sulphureus were 27.4 and 12.77 kg km-1 at the depths of 50-60 m and 60-70 m, respectively. Finally, it was concluded that effective fishing of C. ignobilis and U. sulphureus is affordable at depths above 60-70 m, and it was not different for S. crumenophthalmus at fishing depths.